PENGARUH JUMLAH TENAGA PENDORONG TERHADAP KECEPATAN LORI PADA PENGANGKUTAN KAYU - Apul Sianturi; Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
This investigation was carried out in the: Padangan Forest District, Perum Perhutani Unit II, East Java, employing crews of various sizes, i.e., 4, 5 and 6 men to push the loaded lorries.Lorry speed is influenced by several factor, e.g., slope, crew size, team-work among crew members. The influence of crew size on lorry speed turned out to be insignificant. The average speed of lorries are 3.3 km/hour, 4.7 km/hour, and 4.3 km/hour with standard error of 0.7 km/hour, 0,8 km/hour and 0,9 km/hour for 4, 5 and 6 man, crew, respectively.